Atlas of structural geological interpretation from seismic images - Misra, Achyuta Ayan; Mukherjee, Soumyajit (John Wiley & Sons, 2018)
This comprehensive book deals primarily with reflection seismic data in the hydrocarbon industry. It brings together seismic examples from North and South America, Africa, Europe, Asia and Australia and features contributions from eleven international authors who are experts in their field. It provides structural geological examples with full-color illustrations and explanations so that students and industry professionals can get a better understanding of what they are being taught. It also shows seismic images in black and white print and covers compression related structures. Representing a compilation of examples for different types of geological structures, Atlas of Structural Geological Interpretation from Seismic Images is a quick guide to finding analogous structures. It provides extensive coverage of seismic expression of different geological structures, faults, folds, mobile substrates (shale and salt), tectonic and regional structures, and common pitfalls in interpretation. The book also includes an un-interpreted seismic section for every interpreted section so that readers can feel free to draw their own conclusion as per their conceptualization.--Provided by publisher.